A new mud-nesting Fanged Frog (Anura: Dicroglossidae) from Arunachal Pradesh with notes on L. longchuanensis from India - Boruah, Bitupan; Rajiv, N. V.; Dutta, Sourav; Das, Abhijit (Zootaxa, 2026)
A new species of Limnonectes is described from Namdapha Tiger Reserve, Arunachal Pradesh, northeast India, based on differences in morphological characters and mitochondrial gene 16S rRNA. The genetic divergence of the new species with its congeners of the L. limborgi complex is 2.4–6.8% in the 16S rRNA gene. The new species can be easily differentiated from its congeners by adult snout-vent length range 23.3–35.9 mm, internarial distance greater than inter-upper eyelid width and upper eyelid width, an inverted “V” shaped dermal fold on dorsum, discontinuous dorsolateral folds on dorsum, dark-brown concave line on inter-upper eyelid space. Additionally, the new species exhibits a unique nesting behaviour, constructing mud nest under leaf litter. This study also formally reports L. longchuanensis from India. With the description of this new species and the report of L. longchuanensis, the number of species of the genus currently known from India increases to six.